The Postcolonial Careers of Santha Rama Rau - Burton, Antoinette M., 1961- (Book collections on Project MUSE., 2007)
Antoinette Burton uses a mid-twentieth-century Indian-American author s career to analyze broader issues of postwar America s understanding of itself and the wider world.